Examining nonextensive statistics in relativistic heavy-ion collisions - Simon, Alessandro; Wolschin, Georg (Physical review, 2018)
We show in detailed numerical solutions of the nonlinear Fokker-Planck equation (FPE), which has been associated with nonextensive q statistics, that the available data on rapidity distributions for stopping in relativistic heavy-ion collisions cannot be reproduced with any permitted value of the nonextensivity parameter (1<q<1.5). This casts doubt on the nonextensivity concept that is widely used in relativistic heavy-ion physics.
Gesehen am 16.10.2019